2023
DOI: 10.3390/foods12010211
|View full text |Cite
|
Sign up to set email alerts
|

Oil Bodies from Chia (Salvia hispanica L.) and Camelina (Camelina sativa L.) Seeds for Innovative Food Applications: Microstructure, Composition and Physical Stability

Abstract: Exploring and deciphering the biodiversity of oil bodies (OBs) recovered from oilseeds are of growing interest in the preparation of sustainable, natural and healthy plant-based food products. This study focused on chia (Salvia hispanica L.) and camelina (Camelina sativa L.) seed OBs. A green refinery process including ultrasound to remove mucilage, aqueous extraction by grinding and centrifugation to recover OBs from the seeds was used. The microstructure, composition and physical stability of the OBs were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
(125 reference statements)
2
6
0
Order By: Relevance
“…Camelina seeds are garnering renewed attention due to their rich nutritional profile. Camelina stands out as a leading candidate for use in the bioeconomy thanks to its intriguing fatty acid profiles among oilseeds [19]. Oil (30% to 49%), protein (24% to 31%), carbohydrates, dietary fibers, ω-3 and ω-6 acids, tocopherols, phytosterols, and phenolic compounds, among other nutrients, are abundant in camelina seeds [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Camelina seeds are garnering renewed attention due to their rich nutritional profile. Camelina stands out as a leading candidate for use in the bioeconomy thanks to its intriguing fatty acid profiles among oilseeds [19]. Oil (30% to 49%), protein (24% to 31%), carbohydrates, dietary fibers, ω-3 and ω-6 acids, tocopherols, phytosterols, and phenolic compounds, among other nutrients, are abundant in camelina seeds [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, vitamin E and carotenoids (the precursors of vitamin A) are described to accumulate in plastoglobules inside plastids rather than in cytosolic LDs (Deruere et al, 1994;Vidi et al, 2006;Zita et al, 2022). Some studies reported the presence of tocopherols in seed LDs (Zaaboul et al, 2018;Lopez et al, 2023). It remains to be determined with precision whether plant cytosolic LDs contain other vitamins and which ones.…”
Section: Lds Represent Specialized Storing Compartments For Non-tag N...mentioning
confidence: 99%
“…According to USA dietary guidelines in 2000, chia seeds can be used as a substitute in food products but in smaller quantities, i.e., not more than 48 g/day. Chia seeds are incorporated in various food products such as pasta, biscuits, cereals, cakes, and snacks [134,135]. Chia seeds/gels can be used as an alternative to eggs and fat due to their hydrophilic property.…”
Section: Value-added Food Products and Other Potential Applicationsmentioning
confidence: 99%